Perancangan Prototipe Robot Pembawa Barang Otomatis Berbasis Arduino Uno DIP dengan Sensor Ultrasonic - Azis, Abdul; Emidiana, Emidiana; Azukruf, Fathir (Elektrika, 2023)
The tool used to carry goods is a trolley. To simplify the process of carrying goods using a trolley, the trolley can be combined with robot technology. In order for the trolley robot to see objects or the surrounding atmosphere, it needs a sense that can be integrated with a sensory system that can sense the presence of an object, namely an ultrasonic sensor. An ultrasonic sensor is a device that captures the motion of an object and converts it into a sound reflection that can be read and processed by a computer. This sound reflection is an input signal that will be processed on a computer to produce information that is useful for certain purposes on the system. From the results of the tests that have been carried out, the performance of the Arduino Uno DIP-based automatic robot carrier prototype with ultrasonic sensors is in accordance with the design. Where for advanced control, the ultrasonic sensor still responds well to hand objects, bags, hats, plastic, clothes, and books, at a distance of 50 cm. Then for the right turn and left turn control, the ultrasonic sensor responds well to objects at a distance of 5 cm, and for reverse control, the ultrasonic sensor still responds well to objects at a distance of 11 cm-20.5 cm. Furthermore, the ultasonic sensor still responds well in reading hand objects at a distance of 50 cm, when given a load with a weight of 1.0 kg-3.0 kg, where the prototype still moves forward even though it starts to become unstable and experiences a decrease in speed. When given a load of 3.5 kg, the prototype does not move forward or has an error. So it can be concluded that the maximum load of the goods carrier robot prototype is 3 kg. Keywords: Design, Prototype, Carrier, Arduino, Ultrasonic Sensor. ABSTRAKAlat bantu yang digunakan untuk membawa barang adalah troli. Untuk mempermudah proses membawa barang dengan menggunakan troli, maka troli dapat dikombinasi dengan teknologi robot. Supaya robot troli dapat melihat objek atau suasana sekitarnya dibutuhkan sebuah indra yang dapat terintregasi dengan sistem indra yang dapat merasakan keberadaan suatu objek, yaitu sensor ultrasonik. Sensor ultrasonik merupakan perangkat yang berfungsi menangkap gerak suatu objek dan mengubahnya ke dalam bentuk refleksi bunyi yang dapat dibaca dan diproses oleh komputer. Refleksi bunyi ini merupakan sinyal masukan yang akan diproses pada komputer dapat menghasilkan informasi yang berguna untuk keperluan tertentu pada sistem. Dari hasil pengujian yang telah dilakukan, kinerja prototipe robot pembawa barang otomatis berbasis Arduino Uno DIP dengan sensor ultrasonic sesuai dengan perancangan. Dimana untuk kontrol maju, sensor ultrasonic masih merespon dengan baik terhadap objek tangan, tas, topi, plastik, baju, dan buku, pada jarak 50 cm. Kemudian untuk kontrol belok kanan dan belok kiri, sensor ultrasonic merespon dengan baik terhadap objek pada jarak 5 cm, dan untuk kontrol mundur, sensor ultrasonic masih merespon dengan baik terhadap objek pada jarak 11 cm-20,5 cm. Selanjutnya sensor ultasonic masih merespon dengan baik dalam membaca objek tangan pada jarak 50 cm, saat diberi beban dengan berat 1,0 kg-3,0 kg, dimana prototipe masih bergerak maju walaupun mulai tidak stabil dan mengalami penurunan kecepatan. Pada saat diberi beban 3,5 kg, prototipe tidak bergerak maju atau error. Sehingga dapat disimpulkan bahwa beban maksimal prototipe robot pembawa barang adalah 3 kg.